Pharmacological activities of Oyster mushroom (Pleurotus ostreatus) - Girma Waktola; Tasisa Temesgen (Novel Research in Microbiology Journal)
In this review paper, different characteristics especially medicinal values of Oyster mushroom were described. As a mycological expression, mushrooms are a fruiting body of macro fungi i.e. Basidiomycota that represents only a short reproductive stage in their life cycle. They have a long association with humankind, and provide profound biological and economic impacts. Starting from ancient times, mushrooms are consumed by man with delicacy, due to their good taste and pleasing flavor. Pleurotus ostreatus is an edible mushroom with high nutritional values and biomedical importance's, since it contains a large number of bioactive components that cause development of its therapeutic functions. The bioactive components that are present in Pleurotus ostreatus mushroom comprise: polysaccharides, lipopolysaccharides, proteins, peptides, glycoproteins, nucleosides, triterpenoids, lectins, lipids and their derivatives, in addition of its vital medicinal components beneficial for the human health. Moreover, Pleurotus ostreatus possess several medicinal properties including; anti-arthritic, antitumor, immune-modulatory, antioxidant, anticancer, anti-inflammatory, antigenotoxic, hypo cholesterolaemic, anti-hyperglycaemic, anti-hypertensive, antiplatelet aggregating, antiviral and antimicrobial activities.